Synthesis and Analgesic Effects of 5-[4-(Arylpiperazin-1-yl)alkylamino]-4-benzyl-3-methyl-1,2-oxazin-6-ones - Bebot, Monique; Rubat, Catherine; Coudert, Pascal; Courteix, Christine; Fialip, Joseph; Couquelet, Jacques (Arzneimittelforschung, 2000)
A series of 5-[4-(arylpiperazin-1-yl)alkylamino]-4-benzyl-3-methy1-1,2-oxazin-6-ones was synthesized and evaluated for analgesic activity. The structures of these new oxazine derivatives were confirmed by IR, 1H-NMR spectra and by elemental analysis. The three most active compounds, 3c, 3e and 3g possessed significant antinociceptive effects in the phenylbenzoquin-one-induced wrigthing test (PBQ-test) in mice, with ED50 values ranging from 19.7 to 68.0 mg/kg i.p. In addition these compounds presented a low toxicity (LD50 > 800 mg/kg i.p.) and did not significantly reduce the spontaneous locomotor activity of mice. They interacted in a synergistic manner with morphine but nevertheless each compound presented its own profile. Thus the analgesic activity of 3c and 3e was naloxone sensitive, suggesting in µ, opioidergic mechanism. Otherwise 3c and 3d analgesia was attenuated by oral administration of yohimbine and therefore seemed to be mediated via noradrenergic pathway. Finally, 5-hydroxytryptophan associated to carbidopa only potentiated 3e analgesia, demonstrating an involvement of a serotoninergic mechanism.
Keywords: Analgesics; 5-[4-(Arylpiperazin-1-yl)alkylamino]-4-benzyl-3-methyl-l,2-oxazin-6-ones; analgesic effects, mouse, synthesis